2023
DOI: 10.1002/advs.202207512
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR/Cas9 Genome Editing for Tissue‐Specific In Vivo Targeting: Nanomaterials and Translational Perspective

Abstract: Clustered randomly interspaced short palindromic repeats (CRISPRs) and its associated endonuclease protein, i.e., Cas9, have been discovered as an immune system in bacteria and archaea; nevertheless, they are now being adopted as mainstream biotechnological/molecular scissors that can modulate ample genetic and nongenetic diseases via insertion/deletion, epigenome editing, messenger RNA editing, CRISPR interference, etc. Many Food and Drug Administration‐approved and ongoing clinical trials on CRISPR adopt ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 265 publications
0
5
0
Order By: Relevance
“…They discovered that RNPs exhibited an increased medicinal impact when delivered in EVs as opposed to RNPs alone and that the exosomes’ capacity to target liver cells improved tissue selectivity. This study demonstrated that exosomes from LX-2 cell lines might be used in liver tumor therapies ( Ding et al, 2021 ; Wan et al, 2022 ; Sahel et al, 2023 ).…”
Section: Need For Biomaterials: Advantages Over Other Delivery Methodsmentioning
confidence: 81%
“…They discovered that RNPs exhibited an increased medicinal impact when delivered in EVs as opposed to RNPs alone and that the exosomes’ capacity to target liver cells improved tissue selectivity. This study demonstrated that exosomes from LX-2 cell lines might be used in liver tumor therapies ( Ding et al, 2021 ; Wan et al, 2022 ; Sahel et al, 2023 ).…”
Section: Need For Biomaterials: Advantages Over Other Delivery Methodsmentioning
confidence: 81%
“…According to the above mentioned, CRISPR/Cas9 has brought great hope to overcome the dilemma of liver cancer treatment by directly editing the genes of immune checkpoints or indirectly affecting the expression of immune checkpoints by editing other genes. However, how to implement the strategy of accurately delivering CRISPR/Cas9 components in order to safely and efficiently take its advantages is an interesting but urgent problem to be solved [130,131]. Therefore, we summarize the method of delivering the system in these studies on the immune checkpoint of the system acting on liver cancer, so as to provide reference for future researchers to achieve accurate and safe delivery of the system for immunotherapy [120] with permission from BMJ Publishing Group Ltd. (B) In MAT2A-KO tumors, the portions of CD8+ T cells positive for immune checkpoint markers are significantly depleted.…”
Section: Delivery Strategies Of the Crispr/cas9 On Immune Checkpoints...mentioning
confidence: 99%
“…This streamlines patient enrollment, study design, and personalized treatment [ 162 , 163 , 164 ]. AI has the potential to significantly enhance research, diagnostics, and therapeutics in the fields of exosomes, CAR T-cell therapy, and CRISPR/Cas9 [ 164 , 165 , 166 ].…”
Section: Ai For Drug Deliverymentioning
confidence: 99%
“…This streamlines patient enrollment, study design, and personalized treatment [162][163][164]. AI has the potential to significantly enhance research, diagnostics, and therapeutics in the fields of exosomes, CAR T-cell therapy, and CRISPR/Cas9 [164][165][166]. By utilizing AI's capabilities in data analysis, pattern recognition, and predictive modeling, the development of protein/peptide and gene therapy biologics can be accelerated, and the design and optimization of therapeutic molecules can be more efficient and targeted.…”
Section: Ai Tools For Biologics Product Developmentmentioning
confidence: 99%